RANCANG BANGUN PINTU GESER OTOMATIS BERBASIS MIKRO KONTROLER ARDUINO - Idzani Muttaqin (INFO-TEKNIK, 2018)
The progress of science and technology from time to time is growing rapidly. Iftraced back, first all activities are done manually. Along with technologicaldevelopments, some activities have been converted into an automated system.Like to open a door that requires human labor, now has many doors that can beautomatically opened when there is someone who will enter. But there are fewobstacles, whereas when someone is running quickly it must wait for the door toopen automatically which causes the person to stop first and wait for the door toopen. In this Final Project, ultrasonic sensor (PING) is used to measure visitordistance. Dc motor is used to set the speed of opening the door. The prototype ofautomatic sliding door is controlled using arduino microcontroller. Test resultsshow that the door will open when visitors are in front of the door measured withultrasonic sensor (PING). After the tool testing, the maximum load of the doorthat can be moved by the tool is less than 15 kg. The time it takes the automaticsliding door to close with the maximum load is 3.12 seconds.